Inhaled corticosteroids in asthma and chronic obstructive pulmonary disease combined phenotype: when to use and what to expect? - Srishankar Bairy; Tarun Tiwari; Himanshu Mittal; Neeraj Gupta; Meghana M (Monaldi Archives for Chest Disease)
The term "asthma-chronic obstructive pulmonary disease (COPD) combined phenotype” describes patients with persistent airflow limitation and features of both asthma and COPD. There is a lack of data on effective treatments for this group, often excluded from asthma or COPD trials. Inhaled corticosteroids (ICS) are standard for asthma, while bronchodilators are key for COPD. This study is a prospective interventional study that included 43 patients diagnosed with the asthma-COPD overlap phenotype, as per Sin et al. criteria, who were treated as COPD priorly and followed over one year. These patients received additional treatment with a moderate-dose ICS metered dose inhaler beclamethasone 800 mcg daily, in addition to their optimal inhaled bronchodilator therapy. Follow-up spirometry along with reversibility, fractional exhaled nitric oxide (FeNO), blood investigations like total eosinophil count (TEC) and immunoglobulin E (IgE) were done; sputum eosinophils were measured, and a history of exacerbations was noted. These parameters were compared with baseline values obtained prior to the initiation of ICS to evaluate the impact of the intervention. Among the 43 individuals in the study population, the majority fell within the age group of 60-69 years. The addition of ICS to bronchodilators over a one-year period resulted in significant improvements in their forced expiratory volume in one second. Additionally, there was a notable reduction in the FeNO level, along with decreases in the TEC, serum IgE levels, and sputum eosinophils. Although the number of exacerbations decreased during the study period in this subgroup, this reduction did not reach statistical significance. Based on these findings, the study suggests that ICS should be considered as an adjunct to inhaled bronchodilators for the management of stable COPD patients exhibiting features of the asthma-COPD combined phenotype.